International Conference on Transportation and Development 2022. selected papers from the International Conference on Transportation and Development 2022, Seattle, Washington, May 31-June 3, 2022 - Wei, Heng (Civil engineer) (American Society of Civil Engineers, 2022)
The second volume of the proceedings of the International Conference on Transportation and Development 2022, held in Seattle, Washington, May 31-June 3, 2022. This collection contains 20 peer-reviewed papers on traffic operations and engineering. Topics include: traffic signs and signals; traffic control and speed limits; traffic congestion modeling; and autonomous vehicles.